MicroRNA-100 Suppresses Chronic Vascular Inflammation by Stimulation of Endothelial Autophagy. Issue 3 (2nd February 2018) - Pankratz, Franziska; Hohnloser, Catherine; Bemtgen, Xavier; Jaenich, Caterina; Kreuzaler, Sheena; Hoefer, Imo; Pasterkamp, Gerard; Mastroianni, Justin; Zeiser, Robert; Smolka, Christian; Schneider, Laura; Martin, Julien; et al.
Abstract : Rationale: : The interaction of circulating cells within the vascular wall is a critical event in chronic inflammatory processes, such as atherosclerosis, but the control of the vascular inflammatory state is still largely unclear. Objective: : This study was undertaken to characterize the function of the endothelial-enriched microRNA miR-100 during vascular inflammation and atherogenesis. Methods and Results: : Based on a transcriptome analysis of endothelial cells after miR-100 overexpression, we identified miR-100 as a potent suppressor of endothelial adhesion molecule expression, resulting in attenuated leukocyte–endothelial interaction in vitro and in vivo as shown by flow cytometry and intravital imaging. Mechanistically, miR-100 directly repressed several components of mammalian target of rapamycin complex 1-signaling, including mammalian target of rapamycin and raptor, which resulted in a stimulation of endothelial autophagy and attenuated nuclear factor κB signaling in vitro and in vivo. In a low-density lipoprotein receptor–deficient atherosclerotic mouse model, pharmacological inhibition of miR-100 resulted in enhanced plaque lesion formation and a higher macrophage content of the plaque, whereas a systemic miR-100 replacement therapy had protective effects and attenuated atherogenesis, resulting in a decrease of plaque area by 45%. Finally, analysis of miR-100 expression in >70 samples obtained during carotid endarterectomy revealed that local miR-100 expression was inversely correlated with inflammatory cell content in patients. Conclusions: : In summary, we describe an anti-inflammatory function of miR-100 in the vascular response to injury and inflammation and identify an important novel modulator of mammalian target of rapamycin signaling and autophagy in the vascular system. Our findings of miR-100 as a potential protective anti-athero-miR suggest that the therapeutic replacement of this microRNA could be a potential strategy for the treatment of chronic inflammatory diseases, such as atherosclerosis, in the future. Abstract : Supplemental Digital Content is available in the text.